Stability of Na–Be minerals in late-magmatic fluids of the Ilímaussaq alkaline complex, South Greenland - Markl, Gregor (Geology of Greenland Survey Bulletin, 2001)
Various Na-bearing Be silicates occur in late-stage veins and in alkaline rocks metasomatised by late-magmatic fluids of the Ilímaussaq alkaline complex in South Greenland. First, chkalovite crystallised with sodalite around 600°C at 1 kbar. Late-magmatic assemblages formed between 400 and 200°C and replaced chkalovite or grew in later veins from an H2O-rich fluid. This fluid is also recorded in secondary fluid inclusions in most Ilímaussaq nepheline syenites. The late assemblages comprise chkalovite + ussingite, tugtupite + analcime ± albite, epididymite + albite, bertrandite ± beryllite + analcime, and sphaerobertrandite + albite or analcime(?). Quantitative phase diagrams involving minerals of the Na–Al–Si–O–H–Cl system and various Be minerals show that tugtupite co-exists at 400°C only with very Na-rich or very alkalic fluids [log (aNa+/aH+) > 6–8; log (aBe2+/(aH+)2) > –3]. The abundance of Na-rich minerals and of the NaOH-bearing silicate ussingite indicates the importance of both of these parameters. Water activity and silica activity in these fluids were in the range 0.7–1 and 0.05–0.3, and XNaCl in a binary hydrous fluid was below 0.2 at 400°C. As bertrandite is only stable at < 220°C at 1 kbar, the rare formation of epididymite, eudidymite, bertrandite and sphaerobertrandite by chkalovite-consuming reactions occurred at still lower temperatures and possibly involved fluids of higher silica activity.